Declining Trend of Agriculture Production due to Constriction of National Highway and Railway Line Through the Fertile Agriculture Land in Kashmir Valley: A Study on its Ill Effects on Agriculture and Measures to Regain the Agriculture Production - Mohi Ud Din, Towseef; Patidar, Reena; Afzal, Arjumand (European Journal of Applied Sciences, 2020)
This article furnishes information about the declining trend of agricultural production as a result of large scale construction of railways and national highways. Also it inform about the environmental problems caused by such constructions. The paper also suggests some measures concerning the regain of agricultural productivity.